2017
DOI: 10.1142/s0218339017500115
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model to Study the Impact of Mining Activities and Pollution on Forest Resources and Wildlife Population

Abstract: In this paper, we develop a nonlinear mathematical model that investigates the impact of mining activities and pollution on forest resources and wildlife population. It is assumed that concentration of pollutants grows in the environment at a constant rate and also augments due to different mining activities prevailing in the forest area. The model is formulated in terms of differential equations and analyzed using elements of stability theory and numerical simulation. The obtained results depict that both for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Where M: Health expenditure of an individual h 0 : The initial state of health of the individual B: The budget that the individual has for their expenses z: Externalities caused by mining (pollution) A: Physical and social characteristics of the individual. Jyotsna and Tandon (2017) propose a mathematical model to show the impact of pollution caused by mining on forests and wildlife.…”
Section: The Mining Sector and Co 2 Pollutionmentioning
confidence: 99%
“…Where M: Health expenditure of an individual h 0 : The initial state of health of the individual B: The budget that the individual has for their expenses z: Externalities caused by mining (pollution) A: Physical and social characteristics of the individual. Jyotsna and Tandon (2017) propose a mathematical model to show the impact of pollution caused by mining on forests and wildlife.…”
Section: The Mining Sector and Co 2 Pollutionmentioning
confidence: 99%
“…He assumed that the rate of growth of wildlife population totally depends on forestry biomass. In a similar study, Jyotsna and Tandon [9] investigated a nonlinear mathematical model to check the impact of mining activities and pollution on forest resources and wildlife populations. They applied numerical simulations and element of stability theory to analyze their model.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of mathematical models in terms of nonlinear dynamical system of differential equations is a popular tool for researchers to conduct studies of natural resource systems and their connected different population ecosystems and environment. Out of diverse natural resources, however, many nonlinear research studies concentrate on forest resources systems, where the effects of different population ecosystems and their associated activities have been investigated on forest resources using consumer–resource type interactions (Shukla & Dubey, 1997; Dubey, Upadhyay, & Hussain, 2003; Dubey, Sharma, Sinha, & Shukla, 2009; Shukla, Lata, & Misra, 2011; Misra, Lata, & Shukla, 2014; Misra & Lata, 2015; Jyotsna & Tandon, 2017a, 2017b). Shukla and Dubey (1997), in their nonlinear modeling study on the impact of population growth and its associated pollution on forest resources, found that the conservation of forest resources, along with control over excessive population growth and pollution should be properly addressed to maintain resource biomass at its required level.…”
Section: Introductionmentioning
confidence: 99%
“…They found the extinction of forest resource in the presence of unprecedented industrialization and therefore, suggested for employing control over industrialization growth to establish ecological stability. Recently, Jyotsna and Tandon (2017a and 2017b) demonstrated the behavior of forest resources along with their dependent wildlife and human populations, in the presence of perturbations caused due to mining activities. In these studies, authors qualitatively and quantitatively analyzed the forest resources based model system and obtained relevant conditions to maintain the stability of such type of systems.…”
Section: Introductionmentioning
confidence: 99%